The evaluation of industrial policies for applied scientific research and innovation SMEs: the firm-level economic effects in the Umbrian experience - Ferrucci, Luca; Montanari, Giorgio; Doretti, Marco (Piccola Impresa / Small Business, 2021)
The article aims to analyze and evaluate public financial resources for applied scientific research and innovation provided to small umbrian manufacturing companies over the course of more than a decade (from 2007 to 2018). The evaluation of these policies is particularly important in the context of a territorial context characterized by a proliferation of small businesses, often operating within subcontracting chains on behalf of medium-large exogenous companies. The methodology used is counter-factual model - using a statistical control sample made up of non-beneficiary companies - and the performance variables used refer to turnover, invested capital, employment and profitability. The conclusions show that these public financial resources have had a positive effect, in particular on turnover and employees, and to a much lesser extent on investments and profitability.